Guide to Bikol orthography - Tria, Wilmer Joseph S.; AdN University Research Council (Naga City Ateneo de Naga University Press, 2014)
This guide focuses on orthography so as to be comprehensive and to address the gray areas in spelling Bikol words.
1. Grapheme -- 2. Syllables and syllabication -- 3. Spelling indigenous words -- 4. Spelling assimilated words -- 5. Use of diacritics.
Keywords: Bikol language -- Orthography and spelling; Bikol language -- Grammar